Cultural heritage in the design of sustainable cities - Al Haddad, Mwfeq (project baikal, 2025)
Modeling cities is becoming an increasingly urgent task. The prevailing trend today is the construction of multifactor models using the capabilities of machine processing of big data. Modeling using heuristic algorithms that rely on a human-machine dialogue looks the most promising. The article presents the results of an experiment on the application of the “Great Wall Construction Algorithm” (GWCA) heuristic to simultaneously take into account extremely heterogeneous parameters – energy efficiency of buildings and their cultural and historical value. It is shown that the use of the GWCA heuristic significantly improves the quality of the model.